Web service development as mechanism of interoperability between the Academic Information System (AIS) Mulawarman University and the Higher Education Data Base (PDDIKTI) using academic data from Department of Computer Science and Statistic at Faculty of Mathematic and Natural Science - Dedy Cahyadi (International Journal of Computing and Informatics (IJCANDI), 2016)
Higher Education Data Base (Pangkalan Data Perguruan Tinggi/PDDIKTI) is used by policy makers at Directorate of Higher Education at the Ministry of Research and Higher Education in order to improve the quality, relevance, affordability and equal access to higher education in which sustainable. In fact, the data still need improvements due to several causes such as invalidity, overlapping, and updating problems.  The management of PDDIKTI does not guarantee the validity of data, therefore universities should carry out regular updates to ensure data displayed on PDDIKTI website (http://forlap.ristekdikti.go.id) is legitimate for users who use the data such as HRD staff of companies in recruitment process.Mulawarman University has connected an Academic Information System (AIS) with PDDIKTI by using web service to process data updates. However, the process itself has a long mechanism and resulted in a slow progress because it must pass through several administrative stages ranging from the department, faculty and university. In the process, validity of the data is still on the department’s responsibility.This research has conducted a Proof of Concept (POC) on the use of web service to process data updates on PDDIKTI through AIS. It is carried out only at department level, consequently, the workflow of updates can become shorter and faster. Based on this result, there are two urgent needs that can be proposed to academic policy makers in campus: improved workflow and an updated standard of procedure in data updates from AIS to PDDIKTI.Higher Education Data Base (Pangkalan Data Perguruan Tinggi/PDDIKTI) is used by policy makers at Directorate of Higher Education at the Ministry of Research and Higher Education in order to improve the quality, relevance, affordability and equal access to higher education in which sustainable. In fact, the data still need improvements due to several causes such as invalidity, overlapping, and updating problems.  The management of PDDIKTI does not guarantee the validity of data, therefore universities should carry out regular updates to ensure data displayed on PDDIKTI website (http://forlap.ristekdikti.go.id) is legitimate for users who use the data such as HRD staff of companies in recruitment process.Mulawarman University has connected an Academic Information System (AIS) with PDDIKTI by using web service to process data updates. However, the process itself has a long mechanism and resulted in a slow progress because it must pass through several administrative stages ranging from the department, faculty and university. In the process, validity of the data is still on the department’s responsibility.This research has conducted a Proof of Concept (POC) on the use of web service to process data updates on PDDIKTI through AIS. It is carried out only at department level, consequently, the workflow of updates can become shorter and faster. Based on this result, there are two urgent needs that can be proposed to academic policy makers in campus: improved workflow and an updated standard of procedure in data updates from AIS to PDDIKTI.